A Circular Economy-Based Plastic Waste Management Policy in Indonesia (Compared to China and EU) - Subekti, Rahayu (Faculty of Law, Universitas Sebelas Maret, 2023)
Indonesia is a significant plastic waste producer and has more responsibility. In response, the Indonesian government has released several plastic garbage-related policies. However, the policies are viewed as ineffective. Through the circular economy concept, this study examines potential waste management policies for sustainable development by examining existing policies and comparing China's and the European Union's policies. The study shows that Indonesian waste management is highly dependent on the government. The policy affecting many sectors should require synergic participation from the related stakeholders, namely employers, investors, academicians, and civil society. As learned from these two countries, they have regulations related to an integrated waste management system, so there are no overlapping regulations. Furthermore, Indonesian waste management should consider the availability of a market for environmentally friendly items